BARANG BEKAS SEBAGAI MEDIA PENCIPTAAN KARYA SENI DALAM PEMBELAJARAN SENI RUPA KELAS V SD 1 GRIBIG KUDUS - Rofian, Ari Widyaningrum (Universitas PGRI Semarang, 2015)
Learning to take advantage of scarps?é?á is learning to enhance students' knowledge in the work of art which has its own characteristics. The method in this research is a qualitative approach. Location and objectives this research in SD I Gribig Kudus and learning objectives in this research is art, especially in the use scarps. Students who follow this learning process are a fifth grade student in SD I Gribig Kudus. In a study that has been conducted in SD I Gribig Kudus produces a work by using some of the junk that aesthetic value. Works in both categories can be seen from the manufacturing process, the students in making this work to streamline the predetermined time, the completeness of tools and materials before the process is done by dividing the tasks on each member of?é?á group. The results of student creativity at work is seen from the use of colored paper and combine a color that is pretty neat. In this process, the students easily understand the techniques provided by the teacher. Learning outcomes in the use of second-hand goods in the form of work as meronce necklace of newsprint, the hood of food, toy dragon, ornamental flowers of beverage glass packaging, the tower of a pack of cigarettes, and a lantern from plastic bottles.